Lakon Kalebandu Sajian Ki Mantep Soedharsono Di Mata seorang Pengamat Wayang - Blacius Subono (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2007)
The article entitled pakeliran observation on lakon Kalendu presented by Manteb Sedharsono on 25 March in Taman Budaya Surakarta, studies about problems in relation to garap elements in lakon Kalendu. Problem which is found is how the presented lakon elements are. This study aims to describe garap lakon, catur, sabet, and iringan presented by Manteb Soedharsono in lakon Kalendu. The result shows that presented garap lakon is suitable for the present day. The presented garap catur is, sometimes, brought up exactly and densely, but it can gove an interesting performance. Garap sabet shows that wayang movements in certain condition, event without previous dialogues. Garap iringan is also presented in unity with other elements.Key words: Kalendu, Mantep Soedharsono, shadow play